A case of hereditary hemorrhagic telangiectasia and literature review. Issue 8 (26th June 2022) - Han, Yu; Ding, Bingjie; Li, Mengjuan; Song, Xuewen; Liu, Liu; Zhou, Hu
Abstract: Background: To discuss the clinical features of a patient with hereditary hemorrhagic telangiectasia (HHT). Methods: The clinical data of one patient with HHT are retrospectively analysed. In addition, we review the relevant literature. Results: A 32‐year‐old male patient was admitted to the hematology outpatient department of our hospital and presented with intermittent epistaxis for 24 years. In recent years, he was diagnosed with iron deficiency anemia. The nasal endoscopic examination showed telangiectasia at the front of the right‐middle turbinate and the left nasal cavity. He had ENG genetic mutation positivity. Conclusions: Patients with HHT may suffer from many complications, including bleeding, anemia, iron deficiency, and high‐output heart failure. These patients may have telangiectasias and arteriovenous malformations in various organs. Abstract : Patients with HHT may suffer from many complications, including bleeding, anemia, iron deficiency, and high‐output heart failure. This patient had ENG genetic mutation positivity.